Optimization of Tribological Parameters of Pre-Positioned Wire Based Electron Beam Additive Manufactured Ti-6Al-4V Alloy - A. Manjunath; V. Anandakrishnan; S. Ramachandra; K. Parthiban; S. Sathish (Archives of Metallurgy and Materials, 2022)
The versatile application of titanium alloy in the aerospace industry and it’s hard to machine characteristics focus towards the additive manufacturing. The Ti-6Al-4V alloy is manufactured using the electron beam source with a novel method of prepositioned titanium alloy wires. The tribology of the additive manufactured titanium alloy under dry sliding condition is experimented and analysed using Taguchi technique. The targeted objective of minimum tribological responses are attained with the identified optimal parameters as load – 9.81 N, sliding velocity – 3 m/s, sliding distance – 3000 m for minimum specific wear rate and load – 9.81 N, sliding velocity – 3 m/s, sliding distance – 1000 m for minimum coefficient of friction. Among the parameters tested, load is found to be the dominant factor on the tribology of additively manufactured titanium alloy. The morphological analysis on the worn surface and debris revealed the existence of abrasion, delamination and adhesion wear mechanisms. The increase in the load dominantly showed the appearance of delamination mechanism.